EVALUATION OF EDUCATION PROGRAMMES USING THE BALANCED SCORECARD METHOD - Merdi F. Mamonto; Mohammad Ahmad Bani Amer; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study explores the use of the Balanced Scorecard (BSC) method in evaluating educational programmes to improve the quality and effectiveness of educational institutions. BSC offers a holistic framework by integrating four perspectives-financial, customer, internal processes, and learning and growth-to assess overall performance. In the context of education, the use of BSC enables institutions to assess and align strategic objectives with day-to-day operational performance. The results of the analysis show that BSC implementation can improve accountability, transparency and focus on continuous improvement in educational settings. Despite some implementation challenges, such as the need for management commitment and a rigorous measurement system, BSC proved to be an effective tool in guiding educational strategies towards better outcomes. This study concludes that the adoption of the BSC approach can support educational institutions in facing future challenges and increasing value for all stakeholders.